(untitled) (Hakim: Jurnal Ilmu Hukum dan Sosial, 2026)
The Indonesian Constitution positions the right to food as an essential part of the right to life, welfare, and human dignity. This article analyzes the legal politics of protecting sustainable food agricultural land through the policy of Protected Rice Fields (Lahan Sawah Dilindungi/LSD) and its relationship with Sustainable Food Agricultural Land (Lahan Pertanian Pangan Berkelanjutan/LP2B). The study uses normative juridical research with statutory, conceptual, and descriptive-analytical approaches to examine the 1945 Constitution, Law No. 41 of 2009, Presidential Regulation No. 59 of 2019, ministerial decisions on LSD designation, and relevant legal literature. The findings show that LSD is not an isolated spatial-planning instrument, but a constitutional policy designed to accelerate LP2B protection, restrain agricultural land conversion, and strengthen national food sovereignty. Law No. 41 of 2009 and Presidential Regulation No. 59 of 2019 are normatively aligned because both derive their validity from the constitutional mandate to secure public welfare and the right to food. However, implementation still faces serious challenges, especially mismatch between central LSD maps and local LP2B/spatial plans, uncertainty for business actors, and administrative consequences for land already used before LSD designation. Therefore, responsive legal politics requires synchronization of spatial data, participatory verification, proportional dispute settlement, and balanced protection between food-security interests and legal certainty for citizens.